Facile solid-state synthesis of heteroatom-doped and alkaline-treated bismuth vanadate for photocatalyzing methylene blue degradation and water oxidation. (October 2020) - Wu, Yu-Tzu; Lin, JR-Ying; Lin, Lu-Yin; Chen, Yu-Shiang; Geng, Dong-Sheng
Abstract: Bismuth vanadate (BiVO4 ) with suitable band position and visible light responsive properties has been well adopted as the efficient photocatalyst for organic pollution degradation and water oxidation. However, the traditionally used solution process for synthesizing BiVO4 involving dissolving, reacting, crystallizing, and drying is complex and time-consuming. In this study, a facile solid-state synthesis is proposed to fabricate BiVO4 powders via simply mixing the precursors. Heteroatoms doping and alkaline treatment are also realized on BiVO4 by directly incorporating relevant precursors in the solid solution. Methylene blue degradation under visible light for 80 min is enhanced to 81% when 0.1 M NaOH is used to modify BiVO4, due to the possible development of bismuth oxide/BiVO4 heterojunction and the maintenance of rough surface. On the other hand, the W and Mo co-doped BiVO4 electrode shows a higher photocurrent density of 1.17 mA/cm 2 at 1.23 VRHE than that for the BiVO4 electrode (0.33 mA/cm 2 at 1.23 VRHE ) under AM 1.5 solar simulation, owing to the higher carrier density induced by heteroatom-doping for the former case. Different photocatalytic performances of the heteroatom and the alkaline modified BiVO4 toward methylene blue degradation and water oxidation are inferred to be caused by different material compatibilities and the trade-off of the heterojunction and surface roughness. This work not only provides the facile solid-state synthesis but also gives evidences on the varied photoelectrochemical performances toward photodegradation and water splitting for the BiVO4 photocatalysts modified using different manners.